2003
DOI: 10.1300/j144v09n01_06
|View full text |Cite
|
Sign up to set email alerts
|

From Chemical Ecology to Agronomy: Cropping Systems in the Humid Northeast

Abstract: Crop production in the northeastern North America poses unique challenges in that soils tend to be cool and wet in the spring, and there is only a brief period each summer when sufficient heat is obtained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 171 publications
0
1
0
Order By: Relevance
“…When applied to soybean leaves LCO from B. japonicum caused transient (2Á5 d) increases in photosynthetic rate under growth chamber conditions (Almaraz et al 2007;Khan et al 2008) and increased soybean yield (Â25%) under field conditions (Smith et al 2003;Almaraz et al 2007). While the increase in photosynthetic rate due to the application of bacteria-to-plant signal molecules is new, previous studies have suggested that symbiotic microbes increase plant photosynthetic rates: rhizobia (Maury et al 1993), mycorrhizal fungi (Kucey and Paul 1982), PGPR Bai et al 2003) and bacteria that produce lumichrome (Phillips et al 1999).…”
Section: Industrial Applications and Market Potentialmentioning
confidence: 99%
“…When applied to soybean leaves LCO from B. japonicum caused transient (2Á5 d) increases in photosynthetic rate under growth chamber conditions (Almaraz et al 2007;Khan et al 2008) and increased soybean yield (Â25%) under field conditions (Smith et al 2003;Almaraz et al 2007). While the increase in photosynthetic rate due to the application of bacteria-to-plant signal molecules is new, previous studies have suggested that symbiotic microbes increase plant photosynthetic rates: rhizobia (Maury et al 1993), mycorrhizal fungi (Kucey and Paul 1982), PGPR Bai et al 2003) and bacteria that produce lumichrome (Phillips et al 1999).…”
Section: Industrial Applications and Market Potentialmentioning
confidence: 99%